INTRAOPERATIVE DETECTION OF THE SENTINEL LYMPH NODES IN LUNG CANCER - A. L. Akopov; G. V. Papayan; I. V. Chistyakov (Вестник хирургии имени И.И. Грекова)
An analysis of the scientific data was made. It was used the literature devoted to the intraoperative visualization of the sentinel lymph nodes in patients with lung cancer. Correct detection of such lymph nodes with following pathologic investigation allowed limiting the volume of lympho-dissection in a number of patients. There is the possibility of maximal in-depth study of the sentinel lymph nodes by purposeful application of most sensible pathologic and molecular methods for detection their micro-metastatic lesions. At the same time the treatment strategy and prognosis could be determined. The authors present the results of an application of dye techniques, radioactive preparation and fluorescence imaging for sentinel lymph node detection. Advantages and disadvantages of the methods are shown in the article. There are validated the prospects of technical development, study of information value of new applications and the most perspective method of fluorescence indocyanine green visualization by lymph outflow.